Nutritional problems and their non‐pharmacological treatment in adults undergoing haematopoietic stem cell transplantation—A systematic review. (30th August 2020) - Eglseer, Doris; Seymann, Carola; Lohrmann, Christa; Hoedl, Manuela
Abstract: Objective: This systematic review aimed to identify the most relevant problems related to malnutrition in adult patients undergoing haematopoietic stem cell transplantation (HSCT) and to identify non‐pharmacological interventions to treat these problems. Methods: A systematic search for each research question was performed in MEDLINE, CINAHL, Embase, the Cochrane Library, Google Scholar and reference lists in the period 2009–2019. Results: Six and nine studies were included respectively. Quantitative pooling of data was not possible due to the heterogeneity of the studies. Oral mucositis (OM), nausea/vomiting, diarrhoea and dysgeusia were the most frequently reported nutritional problems. Cryotherapy and laser therapy seem to be effective in the prevention and treatment of OM. Recommendations for or against the use of mouth rinses and light therapy in the treatment of OM cannot be made, as too few studies have been conducted in this area. The evidence for non‐pharmacological treatment options in the case of nausea/vomiting and diarrhoea is rather limited. No study was identified with regard to treatment of dysgeusia. Conclusion: Nutrition in HSCT patients has not yet been studied to a satisfactory extent. There is an urgent need for high‐quality studies to be conducted in this area to optimise the care of patients undergoing haematopoietic stem cell transplantation.